Analisa Perbandingan Pengendali PID pada Motor DC Menggunakan Metode Ziegler-Nichols dan Trial and Error - Refigol Afrawira; Rendi Fajar Gumilang; Sitti Amalia; Sepanur Bandri (Dinasti Research, 2023)
The purpose of this research is to design a PID control on a DC motor using 2 tuning methods, namely Trial & Error and Ziegler-Nichols. The results showed that the Pittman DC Motor system response from the Pittman DC motor was very unstable, in which there were still many oscillations and a very high overshoot value. In the Trial & Error method, the system response value was obtained on the P controller, namely, rise time = 0.000551 s, settling time = 0.00468 s, overshoot = 37.1 %, peak time = 0.972 s, and time delay = 0.00134 s. on the PI controller namely, rise time = 0.000396 s, settling time = 0.00534 s, overshoot = 47.7%, peak time = 1.23 s, and time delay = 0.00102 s. on the PID controller namely, rise time = 0.000223 s, settling time = 0.00502 s, overshoot = 64.6%, peak time = 1.54 s, and time delay = 0.000601 s. In the Ziegler-NIchols method, the response value of the system to the P controller is obtained, namely, rise time = 0.00118 s, settling time = 0.00564 s, overshoot = 15.4%, peak time = 0.178 s, and time delay = 0.00262 s. on the PI controller namely, rise time = 0.000275 s, settling time = 0.00531 s, overshoot = 58.3%, peak time = 1.44 s, and time delay = 0.000767 s. on the PID controller, namely, rise time = 0.00133 s, settling time = 0.00446 s, overshoot = 12.6 %, peak time = 0.0237 s, and time delay = 0.00288 s. The simulation results show that the value for the Ziegler-Nichols tuning method is better than the Trial & Error method, perhaps because the input value for the Trial & Error method is larger.